STUDY ON PERCEIVED ONLINE CONVENIENCE AND CUSTOMER SATISFACTION TOWARD BEHAVIORAL INTENTION IN ONLINE SHOPPING - Indriani, Farida; Nurdianasari, Rista (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the dimensions of online convenience that have an effect and most importantly on the satisfaction and behavioral intentions of a consumer when shopping online. The data source used in this research is primary data. The technique chosen to support research activities related to sampling in this research is the Nonprobability Sampling technique. This research make use of Structural Equation Modeling (SEM) as a statistical instrument in an effort to test various hypotheses that have been determined with the help of AMOS 24 software. The results showed that There is an indirect relationship between perceived convenience online and behavioral intention and there is a direct relationship between online consumer satisfaction and behavioral intention. Based on the research results, it can be proven that all sub-construct dimensions such as access, search, evaluation, attention, transaction, ownership, and post-ownership can represent the main constructs, namely consumers' perceptions of online convenience, especially in Indonesia. Keywords: Perceptions of Online Convenience; Online Consumer Satisfaction; Behavioral Intention; SEM